A kind of preparation method and application of sodium formate

By introducing the process flow of modified activated carbon and modified filter membrane, the problems of low purity and insufficient performance of sodium formate in the prior art are solved, and the preparation of high-purity sodium formate and its high-performance application in drilling fluids are realized.

CN119143593BActive Publication Date: 2025-02-07SHANDONG KERUNDA PETROLEUM TECH CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411599321.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-11-11
Publication Date
2025-02-07
Estimated Expiration
2044-11-11

AI Technical Summary

Technical Problem

The sodium formate prepared in the prior art is not purity enough and its performance is insufficient, making it difficult to meet the high-performance needs of drilling fluids.

Method used

By introducing modified activated carbon and modified filter membrane, the adsorption efficiency of impurities is improved, and the modification process is adopted to obtain high-purity sodium formate and apply it to the drilling fluid.

Benefits of technology

It significantly improves the purity and performance of sodium formate and enhances the performance of drilling fluid, including reducing filtration loss, improving the rolling recovery of rock chips and reducing shale expansion.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The present invention provides a preparation method and application of sodium formate, and relates to the technical field of sodium formate material preparation. The present invention improves the process and improves the impurity adsorption efficiency, introduces modified activated carbon and modified filter membrane, thereby obtaining purified sodium formate, and applies it to drilling fluid to improve various properties of drilling fluid.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of sodium formate material preparation, and in particular to a preparation method and application of sodium formate. Background Art

[0002] Sodium formate is also known as sodium formate. It contains two crystal waters in its crystals, so it is also known as sodium formate dihydrate, sodium formate dihydrate, and sodium formate dihydrate. Sodium formate is the simplest organic carboxylate, which is white crystal or powder with a slight smell of formic acid. It is slightly deliquescent and hygroscopic. It is easily soluble in about 1.3 parts of water and glycerol, slightly soluble in ethanol and octanol, and insoluble in ether. Its aqueous solution is alkaline. Sodium formate decomposes into hydrogen and sodium oxalate when heated, and then generates sodium carbonate. Sodium formate is mainly used to produce sodium hydrosulfite, oxalic acid and formic acid. In the leather industry, it is used as a camouflage acid in the chrome tanning process, a catalyst and a stabilizing synthetic agent, and a reducing agent in the printing and dyeing industry.

[0003] Chinese patent (CN113024353A) discloses a method for preparing sodium formate. The preparation of sodium formate in this patent uses trifluoroacetoacetate ethyl enol sodium salt and formic acid as raw materials, and includes the following steps: A1. Add formic acid to trifluoroacetoacetate ethyl enol sodium salt solution, control the temperature to 10-60°C, and keep the temperature for 2.0-5.0 hours after the addition is completed; A2. Separate the reaction liquid into solid and liquid, and the solid after separation is crude sodium formate. This invention has the advantages of mild reaction, high safety, and basically no three wastes. However, the sodium formate prepared by the prior art still has the problem of insufficient purity and insufficient performance when used.

[0004] Therefore, how to improve the process and enhance the impurity adsorption efficiency, obtain purified sodium formate, and apply it to drilling fluid to improve the various properties of drilling fluid has become the focus of current research. Summary of the invention

[0005] In view of the shortcomings of the prior art, the purpose of the present invention is to provide a method for preparing sodium formate and application thereof, aiming to solve the problem that the sodium formate prepared by the prior art still has insufficient purity and insufficient performance when used.

[0006] The invention improves the process and improves the impurity adsorption efficiency, introduces modified activated carbon and modified filter membrane, thereby obtaining purified sodium formate, and applies the sodium formate to drilling fluid to improve various properties of the drilling fluid.

[0007] The technical solution of the present invention is as follows:

[0008] The first aspect of the present invention provides a method for preparing sodium formate, comprising the following steps: step S1: in parts by weight, 30 parts of sodium hydroxide are added to 100 parts of deionized water in a reaction kettle, stirred and dissolved, then 250 parts of toluene, 3 parts of di(acetylacetone)palladium, and 7 parts of triphenylphosphine are added, the reaction kettle is closed, the air in the reaction kettle is replaced with nitrogen, the temperature is raised to 40° C., carbon monoxide is charged into the reaction kettle, and the reaction is carried out at a pressure of 0.4 MPa for 10 hours; the charging of carbon monoxide is stopped, and the residual carbon monoxide in the kettle is replaced with nitrogen to obtain a layered reaction liquid, the upper toluene layer is recovered, the lower aqueous solution layer is evaporated and concentrated, and dried to obtain crude sodium formate;

[0009] Step S2: In parts by weight, 300 parts of crude sodium formate are added to 600 parts of deionized water, stirred and dissolved at 50° C. for 0.5 h, then 1200 parts of isooctyl alcohol are added, stirred at 80° C. for 1 h, kept warm and allowed to stand for stratification for 1 h, and the oil phase and the aqueous phase are separated, the aqueous phase is passed through modified activated carbon and a modified filter membrane in turn, and then rotary evaporated, cooled, filtered, and dried to obtain purified sodium formate.

[0010] The following are preferred technical solutions of the present invention, but are not intended to limit the technical solutions provided by the present invention. Through the following preferred technical solutions, the objectives and beneficial effects of the present invention can be better achieved and realized.

[0011] As a preferred technical solution of the present invention, the preparation method of the modified activated carbon is as follows: by weight, 20 to 30 parts of activated carbon are added to 100 to 120 parts of deionized water, ultrasonically vibrated for 4 minutes, the temperature was adjusted to 70°C, 10 to 15 parts of polyethylene glycol were added and stirred for 0.5 hours; the temperature was controlled to 50°C, 10 to 15 parts of nano zinc oxide were added, stirred at a speed of 4000r / min for 0.5 hours, the filter residue was dried after filtration, placed in a glass reactor, the glass reactor was placed in a microwave, and microwaved at a frequency of 500w for 10 minutes under nitrogen protection to obtain modified activated carbon.

[0012] As a preferred technical solution of the present invention, the preparation method of the modified filter membrane is as follows: by weight, the PVDF microporous membrane is immersed in 150~200ml of a 1.2% diethylenetriaminepentaacetic acid solution for 20 minutes, and after the immersion, it is placed in an oven at 75°C for heat treatment for 30 minutes to obtain an intermediate membrane; the intermediate membrane is immersed in 150~200ml of a 1.5% polyethyleneimine solution for 10 minutes, and after the immersion, it is placed in an oven at 70°C for heat treatment for 20 minutes to obtain a modified filter membrane.

[0013] The modified activated carbon can be modified by microwave treatment to achieve a better specific surface area and pore diameter, while increasing the micropore volume and improving the adsorption capacity; at the same time, there are a large number of active sites on the surface of the introduced nano zinc oxide, which can form chemical bonds or physical adsorption with impurities to achieve effective removal of impurities; the filter membrane is modified by diethylenetriaminepentaacetic acid, so that the modified filter membrane contains carboxyl, hydroxyl and other groups, which can better adsorb and thus improve the purity.

[0014] The second aspect of the present invention provides the use of sodium formate prepared by the above method, comprising the following steps:

[0015] Step (1): by weight, weigh 45-87 parts of purified sodium formate, add it to 20-30 parts of deionized water, and stir at 2000 r / min for 0.5 h to obtain a purified sodium formate solution;

[0016] Step (2): adding 8 to 11 parts by weight of xanthan gum, 5 to 10 parts by weight of hydroxyethyl cellulose, 10 to 20 parts by weight of graphite and 14 to 22 parts by weight of silicon dioxide to the purified sodium formate solution of step (1), and shearing and stirring the mixture at 2500 r / min for 1 hour to obtain a mixed solution;

[0017] Step (3): Add 4 to 9 parts of a buffer and 1 to 4 parts of an antioxidant to the mixed solution of step (3) by weight, and stir at 10,000 r / min for 0.5 h to obtain a purified sodium formate drilling fluid.

[0018] As a preferred technical solution of the present invention, the hydroxyethyl cellulose is a composite modified hydroxyethyl cellulose; the preparation method of the composite modified hydroxyethyl cellulose is: by weight, 40 parts of 2-acrylamide-2-methylpropane sulfonic acid are weighed and dissolved in 200 parts of deionized water, 10 parts of sodium chloride are added and stirred for 0.5h, the pH is adjusted to 7.4, and then 40 parts of dimethyldiallyl ammonium chloride and 20 parts of grafted modified hydroxyethyl cellulose are added, stirred for 1h to obtain a mixed solution, the mixed solution is transferred to a reactor, nitrogen is introduced for deoxygenation, 4 parts of potassium persulfate are added at 80°C for reaction for 8h, dried, and crushed to obtain the composite modified hydroxyethyl cellulose.

[0019] As a preferred technical solution of the present invention, the preparation method of the grafted modified hydroxyethyl cellulose is as follows: by weight, 20 parts of hydroxyethyl cellulose are added to 100 parts of deionized water, stirred for 0.5 h under a nitrogen atmosphere, 5 parts of ammonium cerium nitrate and 10 parts of methacryloylethyl sulfobetaine are added at 35° C., the pH is adjusted to 7.4, the reaction is carried out for 4 h, and after the reaction is completed, acetone is used for precipitation separation, and the precipitate is dried to obtain the grafted modified hydroxyethyl cellulose.

[0020] As a preferred technical solution of the present invention, the graphite is carboxylated graphite; the preparation method of the carboxylated graphite is as follows: 5 parts of graphite are weighed by weight and dispersed in a mixed solution of 20 parts of concentrated sulfuric acid and 30 parts of nitric acid, ultrasonically dispersed for 1 hour at a power of 800 W, and then reacted at 160° C. for 1.5 hours, and the product is washed with distilled water for multiple times until neutral, filtered, and dried to obtain acidified graphite; 1 part of acidified graphite is weighed and dispersed in 100 parts of N,N-dimethylformamide, and ultrasonically dispersed for 0.5 hour at a power of 600 W to obtain a suspension; 4 parts of dicyclohexylcarbodiimide, 0.4 parts of 4-dimethylaminopyridine, and 10 parts of acrylic acid are added to the suspension, and the reaction is carried out at 90° C. for 20 hours under the protection of a nitrogen atmosphere, and then washed, filtered, and dried to obtain carboxylated graphite.

[0021] As a preferred technical solution of the present invention, the silicon dioxide is amino silicon dioxide.

[0022] As a preferred technical solution of the present invention, the preparation method of the amino silica is as follows: by weight, 3 parts of silica are added to 300 parts of deionized water, ultrasonically dispersed at room temperature for 0.5 hours, and then 3 parts of 3-aminopropyltriethoxysilane are added, and the pH is adjusted to 7.5, and the reaction is stirred at 70°C for 12 hours. After the reaction is completed, centrifugation is performed, and the solid obtained by centrifugation is washed three times with deionized water, and placed in a vacuum drying oven at 120°C for 24 hours to obtain amino silica.

[0023] Preferably, the buffer comprises 3 to 6 parts of potassium carbonate and 1 to 3 parts of potassium bicarbonate.

[0024] Preferably, the antioxidant is selected from any one of aluminum oxide, magnesium oxide, and calcium oxide, or a combination of at least two thereof.

[0025] Compared with the prior art, the present invention has the following beneficial effects:

[0026] (1) The modified activated carbon of the present invention is subjected to microwave modification treatment, so that its specific surface area and diameter of pores can reach a better state, while increasing the volume of micropores and improving the adsorption capacity; at the same time, there are a large number of active sites on the surface of the introduced nano zinc oxide, which can form chemical bonds or physical adsorption with impurities, thereby achieving effective removal of impurities; the filter membrane is modified by diethylenetriaminepentaacetic acid, so that the modified filter membrane contains carboxyl, hydroxyl and other groups, which can better adsorb, thereby improving the purity of sodium formate.

[0027] (2) The present invention adopts purified sodium formate as formate, and uses it together with composite modified hydroxyethyl cellulose, and at the same time, the graphite in the system is carboxylated and the silicon dioxide is amino-modified, so as to prepare purified sodium formate drilling fluid. The drilling fluid can reduce the leakage caused by the development of natural fractures and faults during deep drilling, thereby effectively reducing the filtration loss, and at the same time can also improve the rolling recovery rate of rock cuttings and avoid excessive expansion of shale.

[0028] (3) The present invention reacts the carboxyl group of modified graphite with the amino group of modified silica, and adsorbs them onto different clay particles dispersed during the drilling process, thereby building a bridge structure between the clay particles, plugging the gaps between the particles, reducing the gaps between the clay particles, and playing a role in reducing filtration loss together with the clay particles, thereby improving the surface morphology of the drilling fluid filter cake, making it denser and smoother to achieve the effect of reducing filtration loss. DETAILED DESCRIPTION

[0029] For the convenience of understanding the present invention, the present invention lists the following embodiments. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.

[0030] The sources of some components in the embodiments, comparative examples and application examples are as follows:

[0031] Activated carbon, product number I11113, was purchased from Beijing Inokai Technology Co., Ltd.;

[0032] Polyethylene glycol, product number 20240201, Jiangxi Yipsheng Pharmaceutical Co., Ltd.;

[0033] Nano zinc oxide, product number Z112849, was purchased from Shanghai Aladdin Biochemical Technology Co., Ltd.;

[0034] PVDF microporous membrane, purchased from Jiangsu Nantong Longjin Membrane Technology Co., Ltd.;

[0035] Diethylenetriaminepentaacetic acid, CAS No. 67-43-6, purchased from Shanghai Aladdin Biochemical Technology Co., Ltd.;

[0036] Polyethyleneimine, CAS No. 9002-98-6, was purchased from Shanghai Aladdin Biochemical Technology Co., Ltd.;

[0037] Sodium formate, CAS No. 141-53-7, purchased from Shanghai Aladdin Biochemical Technology Co., Ltd.;

[0038] Xanthan gum, CAS No. 11138-66-2, purchased from Shanghai Aladdin Biochemical Technology Co., Ltd.;

[0039] Hydroxyethyl cellulose, CAS No. 9004-62-0, was purchased from Shanghai Aladdin Biochemical Technology Co., Ltd.;

[0040] Graphite, CAS No. 7782-42-5, was purchased from Shanghai Aladdin Biochemical Technology Co., Ltd.;

[0041] Silicon dioxide, CAS No. 7631-86-9, was purchased from Shanghai Aladdin Biochemical Technology Co., Ltd.;

[0042] Potassium carbonate, CAS No. 584-08-7, purchased from Shanghai Aladdin Biochemical Technology Co., Ltd.;

[0043] Potassium bicarbonate, CAS No. 298-14-6, purchased from Shanghai Aladdin Biochemical Technology Co., Ltd.;

[0044] Magnesium oxide, CAS No. 1309-48-4, was purchased from Shanghai Aladdin Biochemical Technology Co., Ltd.

[0045] Embodiment 1, this embodiment provides a method for preparing sodium formate, comprising the following steps:

[0046] Preparation of modified activated carbon: by weight, add 30 parts of activated carbon to 120 parts of deionized water, ultrasonically vibrate for 4 minutes, adjust the temperature to 70°C, add 10-15 parts of polyethylene glycol and stir for 0.5 hours; control the temperature to 50°C, add 15 parts of nano zinc oxide, stir at a speed of 4000r / min for 0.5 hours, filter and dry the residue, place it in a glass reactor, put the glass reactor into a microwave, and microwave it at a frequency of 500w for 10 minutes under nitrogen protection to obtain modified activated carbon;

[0047] Preparation of modified filtration membrane: Based on parts by weight, the PVDF microporous membrane was immersed in 200 ml of 1.2% diethylenetriaminepentaacetic acid solution for 20 minutes, and then heat-treated in a 75°C oven for 30 minutes to obtain an intermediate membrane; the intermediate membrane was immersed in 200 ml of 1.5% polyethyleneimine solution for 10 minutes, and then heat-treated in a 70°C oven for 20 minutes to obtain a modified filtration membrane.

[0048] Step S1: In parts by weight, 30 parts of sodium hydroxide are added to 100 parts of deionized water in a reactor, stirred to dissolve, and then 250 parts of toluene, 3 parts of di(acetylacetone)palladium, and 7 parts of triphenylphosphine are added, the reactor is closed, the air in the reactor is replaced with nitrogen, the temperature is raised to 40° C., carbon monoxide is charged into the reactor, and the reaction is carried out at a pressure of 0.4 MPa for 10 hours; the charging of carbon monoxide is stopped, and the residual carbon monoxide in the reactor is replaced with nitrogen to obtain a layered reaction solution, the upper toluene layer is recovered, the lower aqueous solution layer is evaporated and concentrated, and dried to obtain crude sodium formate;

[0049] Step S2: In parts by weight, 300 parts of crude sodium formate are added to 600 parts of deionized water, stirred and dissolved at 50° C. for 0.5 h, then 1200 parts of isooctyl alcohol are added, stirred at 80° C. for 1 h, kept warm and allowed to stand for stratification for 1 h, and the oil phase and the aqueous phase are separated, the aqueous phase is passed through modified activated carbon and a modified filter membrane in turn, and then rotary evaporated, cooled, filtered, and dried to obtain purified sodium formate.

[0050] Embodiment 2, this embodiment provides a method for preparing sodium formate, comprising the following steps:

[0051] Preparation of modified activated carbon: by weight, add 20 parts of activated carbon to 100 parts of deionized water, ultrasonically vibrate for 4 minutes, adjust the temperature to 70°C, add 10 parts of polyethylene glycol and stir for 0.5 hours; control the temperature to 50°C, add 10 parts of nano zinc oxide, stir at a speed of 4000r / min for 0.5 hours, filter and dry the residue, place it in a glass reactor, put the glass reactor into a microwave, and microwave it at a frequency of 500w for 10 minutes under nitrogen protection to obtain modified activated carbon;

[0052] Preparation of modified filtration membrane: Based on parts by weight, the PVDF microporous membrane was immersed in 150 ml of a 1.2% mass concentration diethylenetriaminepentaacetic acid solution for 20 minutes, and then placed in a 75°C oven for heat treatment for 30 minutes to obtain an intermediate membrane; the intermediate membrane was immersed in 150 ml of a 1.5% mass concentration polyethyleneimine solution for 10 minutes, and then placed in a 70°C oven for heat treatment for 20 minutes to obtain a modified filtration membrane.

[0053] Step S1: In parts by weight, 30 parts of sodium hydroxide are added to 100 parts of deionized water in a reactor, stirred to dissolve, and then 250 parts of toluene, 3 parts of di(acetylacetone)palladium, and 7 parts of triphenylphosphine are added, the reactor is closed, the air in the reactor is replaced with nitrogen, the temperature is raised to 40° C., carbon monoxide is charged into the reactor, and the reaction is carried out at a pressure of 0.4 MPa for 10 hours; the charging of carbon monoxide is stopped, and the residual carbon monoxide in the reactor is replaced with nitrogen to obtain a layered reaction solution, the upper toluene layer is recovered, the lower aqueous solution layer is evaporated and concentrated, and dried to obtain crude sodium formate;

[0054] Step S2: In parts by weight, 300 parts of crude sodium formate are added to 600 parts of deionized water, stirred and dissolved at 50° C. for 0.5 h, then 1200 parts of isooctyl alcohol are added, stirred at 80° C. for 1 h, kept warm and allowed to stand for stratification for 1 h, and the oil phase and the aqueous phase are separated, the aqueous phase is passed through modified activated carbon and a modified filter membrane in turn, and then rotary evaporated, cooled, filtered, and dried to obtain purified sodium formate.

[0055] Embodiment 3, this embodiment provides a method for preparing sodium formate, comprising the following steps:

[0056] Preparation of modified activated carbon: by weight, add 25 parts of activated carbon to 110 parts of deionized water, ultrasonically vibrate for 4 minutes, adjust the temperature to 70°C, add 12 parts of polyethylene glycol and stir for 0.5 hours; control the temperature to 50°C, add 14 parts of nano zinc oxide, stir at a speed of 4000r / min for 0.5 hours, filter and dry the residue, place it in a glass reactor, put the glass reactor into a microwave, and microwave it at a frequency of 500w for 10 minutes under nitrogen protection to obtain modified activated carbon;

[0057] Preparation of modified filtration membrane: Based on parts by weight, the PVDF microporous membrane was immersed in 180 ml of a 1.2% mass concentration diethylenetriaminepentaacetic acid solution for 20 minutes, and then placed in a 75°C oven for heat treatment for 30 minutes to obtain an intermediate membrane; the intermediate membrane was immersed in 180 ml of a 1.5% mass concentration polyethyleneimine solution for 10 minutes, and then placed in a 70°C oven for heat treatment for 20 minutes to obtain a modified filtration membrane.

[0058] Step S1: In parts by weight, 30 parts of sodium hydroxide are added to 100 parts of deionized water in a reactor, stirred to dissolve, and then 250 parts of toluene, 3 parts of di(acetylacetone)palladium, and 7 parts of triphenylphosphine are added, the reactor is closed, the air in the reactor is replaced with nitrogen, the temperature is raised to 40° C., carbon monoxide is charged into the reactor, and the reaction is carried out at a pressure of 0.4 MPa for 10 hours; the charging of carbon monoxide is stopped, and the residual carbon monoxide in the reactor is replaced with nitrogen to obtain a layered reaction solution, the upper toluene layer is recovered, the lower aqueous solution layer is evaporated and concentrated, and dried to obtain crude sodium formate;

[0059] Step S2: In parts by weight, 300 parts of crude sodium formate are added to 600 parts of deionized water, stirred and dissolved at 50° C. for 0.5 h, then 1200 parts of isooctyl alcohol are added, stirred at 80° C. for 1 h, kept warm and allowed to stand for stratification for 1 h, and the oil phase and the aqueous phase are separated, the aqueous phase is passed through modified activated carbon and a modified filter membrane in turn, and then rotary evaporated, cooled, filtered, and dried to obtain purified sodium formate.

[0060] Comparative Example 1

[0061] This comparative example provides a method for preparing sodium formate, which is different from Example 1 in that step S2 does not use a modified filtration membrane, and other conditions are the same as those in Example 1.

[0062] Comparative Example 2

[0063] This comparative example provides a method for preparing sodium formate, which differs from Example 1 in that modified activated carbon is not used in step S2, and other conditions are the same as those in Example 1.

[0064] Comparative Example 3

[0065] This comparative example provides a method for preparing sodium formate, which is different from Example 1 in that modified activated carbon and modified filter membrane are not used in step S2, and other conditions are the same as those in Example 1.

[0066] The sodium formate performance provided in the above embodiments and comparative examples was tested, and the testing method was as follows:

[0067] Purity of sodium formate: Tested in accordance with the requirements of "HG / T 5390-2018 Sodium Formate for Industrial Use".

[0068] The above performance test data is shown in Table 1:

[0069] Table 1 Sodium formate performance test results

[0070]

[0071] Compared with Example 1, if the modified filter membrane is not used, the purity of sodium formate decreases (Comparative Example 1); compared with Example 1, if the modified activated carbon is not used, the purity of sodium formate decreases (Comparative Example 2); compared with Example 1, if the modified activated carbon and the modified filter membrane are not used, the purity of sodium formate decreases (Comparative Example 3).

[0072] Preparation of composite modified hydroxyethyl cellulose: In parts by weight, 20 parts of hydroxyethyl cellulose (CAS No. 9004-62-0) are added to 100 parts of deionized water, stirred for 0.5 h under a nitrogen atmosphere, 5 parts of ammonium cerium nitrate (CAS No. 16774-21-3) and 10 parts of methacryloylethyl sulfobetaine (CAS No. 3637-26-1) are added at 35°C, the pH is adjusted to 7.4, and the reaction is carried out for 4 h. After the reaction is completed, acetone (CAS No. 67-64-1) is used for precipitation separation, and the precipitate is dried to obtain grafted modified hydroxyethyl cellulose. Weigh 40 parts of 2-acrylamide-2-methylpropanesulfonic acid (CAS No. 15214-89-8) and dissolve them in 200 parts of deionized water, add 10 parts of sodium chloride (CAS No. 7647-14-5) and stir for 0.5 h, adjust the pH to 7.4, then add 40 parts of dimethyldiallylammonium chloride (CAS No. 7398-69-8) and 20 parts of grafted modified hydroxyethyl cellulose, stir for 1 h to obtain a mixed solution, transfer the mixed solution to a reactor, introduce nitrogen to deoxygenate, add 4 parts of potassium persulfate (CAS No. 7727-21-1) at 80°C and react for 8 h, dry, and crush to obtain composite modified hydroxyethyl cellulose.

[0073] Preparation of carboxylated graphite: Weigh 5 parts of graphite (CAS No. 7782-42-5) by weight and disperse them in a mixture of 20 parts of concentrated sulfuric acid (CAS No. 7664-93-9) and 30 parts of nitric acid (CAS No. 7697-37-2), and ultrasonically disperse them at a power of 800 W for 1 hour, then react at 160°C for 1.5 hours, wash the product with distilled water several times until it is neutral, filter, and dry to obtain acidified graphite; weigh 1 part of acidified graphite and disperse it in 100 parts of N , N-dimethylformamide (CAS No. 68-12-2), ultrasonically disperse at a power of 600 W for 0.5 h to obtain a suspension; 4 parts of dicyclohexylcarbodiimide (CAS No. 538-75-0), 0.4 parts of 4-dimethylaminopyridine (CAS No. 1122-58-3), and 10 parts of acrylic acid (CAS No. 79-10-7) were added to the suspension, and reacted at 90 ° C for 20 h under nitrogen atmosphere protection, washed, filtered, and dried to obtain carboxylated graphite.

[0074] Preparation of amino silica: In parts by weight, 3 parts of silica (CAS No. 7631-86-9) were added to 300 parts of deionized water, and ultrasonically dispersed at room temperature for 0.5 h. Then, 3 parts of 3-aminopropyltriethoxysilane (CAS No. 919-30-2) were added, and the pH was adjusted to 7.5. The reaction was stirred at 70°C for 12 h. After the reaction was completed, centrifugation was performed. The solid obtained by centrifugation was washed three times with deionized water and dried in a vacuum drying oven at 120°C for 24 h to obtain amino silica.

[0075] Application Example 1

[0076] An application of sodium formate in drilling fluid comprises the following steps:

[0077] Step (1): by weight, weigh 75 parts of commercially available sodium formate and add them to 25 parts of deionized water, and stir at 2000 r / min for 0.5 h to obtain a sodium formate solution;

[0078] Step (2): Add 10 parts by weight of xanthan gum, 8 parts by weight of commercially available hydroxyethyl cellulose, 12 parts by weight of commercially available graphite and 18 parts by weight of commercially available silicon dioxide to the sodium formate solution of step (1), and stir the mixture at 2500 r / min for 1 hour to obtain a mixed solution;

[0079] Step (3): Add 4 parts of potassium carbonate, 2 parts of potassium bicarbonate and 3 parts of magnesium oxide to the mixed solution described in step (3) by weight, and stir at 10000 r / min for 0.5 h to obtain sodium formate drilling fluid.

[0080] Application Example 2

[0081] An application of sodium formate in drilling fluid is different from Application Example 1 in that the purified sodium formate prepared in Example 1 is used instead of commercially available sodium formate, and other conditions are the same as those in Application Example 1.

[0082] Application Example 3

[0083] An application of sodium formate in drilling fluid is different from Application Example 1 in that composite modified hydroxyethyl cellulose is used to replace commercially available hydroxyethyl cellulose, and other conditions are the same as those in Application Example 1.

[0084] Application Example 4

[0085] An application of sodium formate in drilling fluid is different from Application Example 1 in that carboxylated graphite is used instead of commercially available graphite, and other conditions are the same as those in Application Example 1.

[0086] Application Example 5

[0087] An application of sodium formate in drilling fluid is different from Application Example 1 in that amino silicon dioxide is used instead of commercially available silicon dioxide, and other conditions are the same as those in Application Example 1.

[0088] Application Example 6

[0089] An application of sodium formate in drilling fluid, which differs from Application Example 1 in that purified sodium formate is used instead of commercially available sodium formate, composite modified hydroxyethyl cellulose is used instead of commercially available hydroxyethyl cellulose, carboxylated graphite is used instead of commercially available graphite, and amino silicon dioxide is used instead of commercially available silicon dioxide, and other conditions are the same as those in Application Example 1.

[0090] The performance of the sodium formate drilling fluid provided in the above application example was tested, and the test method was as follows:

[0091] (1) HTHP filtration loss test:

[0092] The test was carried out with reference to the requirements of GB / T 16783.1-2014 Field testing of drilling fluids in the petroleum and natural gas industry Part 1: Water-based drilling fluids.

[0093] (2) Cuttings rolling recovery rate test:

[0094] The test was carried out with reference to the requirements of "NB / T 10121-2018 Evaluation Method for Shale Inhibition of Drilling Fluids".

[0095] (3) Shale expansion rate test:

[0096] The test was carried out with reference to the requirements of "NB / T 10121-2018 Evaluation Method for Shale Inhibition of Drilling Fluids".

[0097] The above performance test data is shown in Table 1:

[0098] Table 1 Performance test results

[0099]

[0100] The sodium formate drilling fluid of Application Example 1 does not adopt the technical points of the present invention, and its performance is poor, with an API filtration loss of 5.8 ml, a rock cuttings rolling recovery rate of 85.1%, and a shale expansion rate of 5.8%; compared with Application Example 1, if purified sodium formate is used instead of commercial sodium formate, the shale expansion rate is reduced (Application Example 2); compared with Application Example 1, if composite modified hydroxyethyl cellulose is used instead of commercial hydroxyethyl cellulose, the filtration loss is reduced (Application Example 3); compared with Application Example 1, if carboxylated graphite is used instead of commercial graphite, the shale expansion rate is reduced. The shale expansion rate is low and the rock cuttings rolling recovery rate is improved (Application Example 4); compared with Application Example 1, if amino silica is used instead of commercially available silica, the shale expansion rate is reduced and the rock cuttings rolling recovery rate is improved (Application Example 5); compared with Application Example 1, if purified sodium formate is used instead of commercially available sodium formate, composite modified hydroxyethyl cellulose is used instead of commercially available hydroxyethyl cellulose, carboxylated graphite is used instead of commercially available graphite, and amino silica is used instead of commercially available silica, the filtration loss is reduced, the rock cuttings rolling recovery rate is improved, and the shale expansion rate is reduced (Application Example 6).

[0101] The applicant declares that the present invention uses the above embodiments to illustrate the detailed process flow of the present invention, but the present invention is not limited to the above detailed process flow, that is, it does not mean that the present invention must rely on the above detailed process flow to be implemented. Those skilled in the art should understand that any improvement of the present invention falls within the protection scope and disclosure scope of the present invention.

Claims

1. A method for preparing sodium formate, characterized in that: The following steps are involved: Step S1: In parts by weight, 30 parts of sodium hydroxide are added to 100 parts of deionized water in a reactor, stirred to dissolve, and then 250 parts of toluene, 3 parts of di(acetylacetone)palladium, and 7 parts of triphenylphosphine are added, the reactor is closed, the air in the reactor is replaced with nitrogen, the temperature is raised to 40° C., carbon monoxide is charged into the reactor, and the reaction is carried out at a pressure of 0.4 MPa for 10 hours; the charging of carbon monoxide is stopped, and the residual carbon monoxide in the reactor is replaced with nitrogen to obtain a layered reaction solution, the upper toluene layer is recovered, the lower aqueous solution layer is evaporated and concentrated, and dried to obtain crude sodium formate; Step S2: adding 300 parts of crude sodium formate to 600 parts of deionized water by weight, stirring and dissolving at 50° C. for 0.5 h, then adding 1200 parts of isooctyl alcohol, stirring at 80° C. for 1 h, keeping warm and standing for stratification for 1 h, separating to obtain an oil phase and an aqueous phase, passing the aqueous phase through modified activated carbon and a modified filter membrane in sequence, and then rotary evaporating, cooling, filtering, and drying to obtain purified sodium formate; The preparation method of the modified activated carbon in step S2 is as follows: by weight, 20 to 30 parts of activated carbon are added to 100 to 120 parts of deionized water, ultrasonically vibrated for 4 minutes, the temperature was adjusted to 70°C, 10 to 15 parts of polyethylene glycol were added and stirred for 0.5 hours; the temperature was controlled to 50°C, 10 to 15 parts of nano zinc oxide were added, and the mixture was stirred at a speed of 4000 r / min for 0.5 hours, and the residue was dried after filtration and placed in a glass reactor, the glass reactor was placed in a microwave, and microwaved at a frequency of 500w for 10 minutes under nitrogen protection to obtain modified activated carbon; The preparation method of the modified filter membrane is as follows: by weight, a PVDF microporous membrane is immersed in 150-200 ml of a 1.2% diethylenetriamine pentaacetic acid solution for 20 minutes, and after the immersion, it is placed in an oven at 75°C for heat treatment for 30 minutes to obtain an intermediate membrane; the intermediate membrane is immersed in 150-200 ml of a 1.5% polyethyleneimine solution for 10 minutes, and after the immersion, it is placed in an oven at 70°C for heat treatment for 20 minutes to obtain a modified filter membrane.

2. An application of sodium formate prepared by the method according to claim 1, characterized in that: The steps include: Step (1): by weight, weigh 45-87 parts of purified sodium formate, add it to 20-30 parts of deionized water, and stir at 2000 r / min for 0.5 h to obtain a purified sodium formate solution; Step (2): adding 8 to 11 parts by weight of xanthan gum, 5 to 10 parts by weight of hydroxyethyl cellulose, 10 to 20 parts by weight of graphite and 14 to 22 parts by weight of silicon dioxide to the purified sodium formate solution of step (1), and shearing and stirring the mixture at 2500 r / min for 1 hour to obtain a mixed solution; Step (3): adding 4 to 9 parts of a buffer and 1 to 4 parts of an antioxidant to the mixed solution of step (3) by weight, stirring at 10,000 r / min for 0.5 h to obtain a purified sodium formate drilling fluid; The hydroxyethyl cellulose is a composite modified hydroxyethyl cellulose; the preparation method of the composite modified hydroxyethyl cellulose is as follows: by weight, 40 parts of 2-acrylamide-2-methylpropane sulfonic acid are weighed and dissolved in 200 parts of deionized water, 10 parts of sodium chloride are added and stirred for 0.5 hours, the pH is adjusted to 7.4, and then 40 parts of dimethyldiallyl ammonium chloride and 20 parts of grafted modified hydroxyethyl cellulose are added and stirred for 1 hour to obtain a mixed solution, the mixed solution is transferred to a reaction kettle, nitrogen is introduced for deoxygenation, 4 parts of potassium persulfate are added at 80° C. for reaction for 8 hours, and the mixture is dried and crushed to obtain the composite modified hydroxyethyl cellulose; The preparation method of the grafted modified hydroxyethyl cellulose is as follows: by weight, 20 parts of hydroxyethyl cellulose are added to 100 parts of deionized water, stirred for 0.5 hours under a nitrogen atmosphere, 5 parts of ammonium cerium nitrate and 10 parts of methacryloylethyl sulfobetaine are added at 35° C., the pH is adjusted to 7.4, the reaction is carried out for 4 hours, and after the reaction is completed, acetone is used for precipitation separation, and the precipitate is dried to obtain the grafted modified hydroxyethyl cellulose; The graphite is carboxylated graphite; the preparation method of the carboxylated graphite is as follows: weigh 5 parts of graphite by weight and disperse them in a mixed solution of 20 parts of concentrated sulfuric acid and 30 parts of nitric acid, ultrasonically disperse them at a power of 800 W for 1 hour, and then react them at 160° C. for 1.5 hours, wash the product with distilled water for multiple times until it is neutral, filter it, and dry it to obtain acidified graphite; weigh 1 part of acidified graphite and disperse it in 100 parts of N,N-dimethylformamide, ultrasonically disperse it at a power of 600 W for 0.5 hour to obtain a suspension; add 4 parts of dicyclohexylcarbodiimide, 0.4 parts of 4-dimethylaminopyridine, and 10 parts of acrylic acid to the suspension, react them at 90° C. for 20 hours under the protection of a nitrogen atmosphere, wash, filter it, and dry it to obtain carboxylated graphite; The silicon dioxide is amino silicon dioxide; The preparation method of the amino silicon dioxide is as follows: by weight, 3 parts of silicon dioxide are added to 300 parts of deionized water, ultrasonically dispersed at room temperature for 0.5 hours, then 3 parts of 3-aminopropyltriethoxysilane are added, and the pH is adjusted to 7.5, and the reaction is stirred at 70° C. for 12 hours. After the reaction is completed, centrifugation is performed, and the solid obtained by centrifugation is washed three times with deionized water, and placed in a vacuum drying oven at 120° C. for 24 hours to obtain the amino silicon dioxide; The buffer comprises 3 to 6 parts of potassium carbonate and 1 to 3 parts of potassium bicarbonate; The antioxidant is selected from any one of aluminum oxide, magnesium oxide, and calcium oxide, or a combination of at least two of them.

Citation Information

Patent Citations

  • Reverse-direction tape translation

    CA919302A

  • Preparation method of sodium formate

    CN113024353A

  • Method for preparing sodium formate by using carbon monoxide under palladium catalysis

    CN102936193A

  • Purification and decolorization method of formamide synthesis byproduct sodium formate waste salt

    CN116120166A